2021
DOI: 10.3390/polym13203462
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals Investigation Behavior on Azo-Based Compounds: A Review

Abstract: Liquid crystal is an intermediate phase between the crystalline solid and an isotropic liquid, a very common substance in our daily lives. Two major classes of liquid crystal are lyotropic, where a liquid crystal is dissolved in a specific solvent under a particular concentration and thermotropic, which can be observed under temperature difference. This review aims to understand how a structure of a certain azo compound might influence the liquid crystal properties. A few factors influence the formation of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Azo polymers are holographic polymer materials composed of photoisomeric molecules and have both cis and trans isomer structures [ 25 , 26 , 27 ], which can be converted into each other when irradiated by light of specific wavelengths. Azo materials are easy to combine with modified components to form azo supramolecular polymers, azo compound liquid crystals, and so on [ 28 ]. When azo-benzene is introduced into the liquid crystal system, the photoinduced change in the azo-benzene molecular shape changes the arrangement of the surrounding liquid crystal molecules, which means that the change in the molecular arrangement will be amplified due to cooperative motion, which can realize image storage in the early stage [ 29 ].…”
Section: Polymers For Holographic Recordingmentioning
confidence: 99%
“…Azo polymers are holographic polymer materials composed of photoisomeric molecules and have both cis and trans isomer structures [ 25 , 26 , 27 ], which can be converted into each other when irradiated by light of specific wavelengths. Azo materials are easy to combine with modified components to form azo supramolecular polymers, azo compound liquid crystals, and so on [ 28 ]. When azo-benzene is introduced into the liquid crystal system, the photoinduced change in the azo-benzene molecular shape changes the arrangement of the surrounding liquid crystal molecules, which means that the change in the molecular arrangement will be amplified due to cooperative motion, which can realize image storage in the early stage [ 29 ].…”
Section: Polymers For Holographic Recordingmentioning
confidence: 99%
“…Incorporation of a photoresponsive unit in soft materials such as liquid crystals (LCs) provide stimuli responsive materials, which can be used for various optoelectronic applications. Over the years, a variety of multiple azoarene based liquid crystals have been prepared where azoarenes act both as mesogen and as the photoresponsive component [33–34] . The most recent reports (2020–2021) of multiazoarene based liquid crystals are A‐43 , [35] A‐44 [36] and A‐45 [37] .…”
Section: Type‐1: Linear Branched and Core‐based Multiazoarene Systemsmentioning
confidence: 99%
“…Over the years, a variety of multiple azoarene based liquid crystals have been prepared where azoarenes act both as mesogen and as the photoresponsive component. [33][34] The most recent reports (2020-2021) of multiazoarene based liquid crystals are A-43, [35] A-44 [36] and A-45. [37] Supramolecular H-bonded bent shaped liquid crystals containing two azoarene units such as A-46 and A-47 are also known (Figure 8).…”
Section: Photoisomerization and Thermal Relaxation Related Propertiesmentioning
confidence: 99%
“…In this Special Issue, 33 original articles have been published on various topics, including the preparation, characterization, and some examples of application of polymeric materials. This issue includes review articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ] and research articles [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%
“…The relationship between the structure and properties of azo-compound-based liquid crystals was described by Razali and Jamain [ 2 ]. In the paper, they have demonstrated that few factors influenced on the formation of different liquid crystals: the length of the alkyl terminal chain, inter/intra-molecular interaction, presence of spacer, spacer length, polarization effects, odd-even effects, and the presence of an electron-withdrawing group or an electron-donating group.…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%